ANALYSIS OF WEAKNESSES OF COASTAL COMMUNITY ECONOMY EMPOWERMENT PROGRAM (PEMP) AND NATIONAL PROGRAM OF COMMUNITY EMPOWERMENT OF INDEPENDENT MARINE AND FISHERIES (PNPM-MKP) ON TRADITIONAL FISHERMEN IN INDONESIA - Bengkel Ginting; M. Arif Nasution; Subhilhar; Hamdani Harahap (Junior Scientific Researcher, 2018)
Indonesia has an abundant fisheries resource. The potential has not been well this is marked by the small contribution of marine and fishery sector to the national income of only 14.7% of the total gross domestic product (GDP), compared to other countries. The dramatic phenomenon between the potential and utilization of marine resources implies to the predominant level of coastal communities who mostly work as fishermen at sea. In order to go to sea with a simple technology also with low human resources make the living standard of traditional fishermen may be categorized as poor. When compared to other farming groups in the agricultural sector, traditional fishermen are among the poorest. With an already many government empowerment programs, yet it has not managed to raise the standard of living for the traditional fishermen. The research is aimed to describe the implementation and weakness of Coastal Community Economy Empowerment Program (PEMP) and National Program of Community Empowerment of Independent Marine and Fisheries (PNPM-MKP) on the traditional fishermen of Percut Village, Percut Sei Tuan in North Sumatra, Indonesia. Type of research is descriptive with 10 traditional fishermen, the fishermen group committee and the marine and fisheries department’s officials. Data were collected by observation, in-depth interview and focus group discussion (FGD). The result of the study of socio-economic condition of traditional fishermen of Percut Village is badly seen from the indicators of housing and sanitation that are not suitable for healthy living, limited fishing equipment and over fishing catching areas.